Cold but not sympathomimetics activates human brown adipose tissue in vivo - Cypess, Aaron M. (National Academy of Sciences, 2012)
As potential activators of brown adipose tissue (BAT), mild cold exposure and sympathomimetic drugs have been considered as treatments for obesity and diabetes, but whether they activate the same pathways is unknown. In 10 healthy human volunteers, we found that the sympathomimetic ephedrine raised blood pressure, heart rate, and energy expenditure, and increased multiple circulating metabolites, including glucose, insulin, and thyroid hormones. Cold exposure also increased blood pressure and energy expenditure, but decreased heart rate and had little effect on metabolites. Importantly, cold increased BAT activity as measured by (18)F-fluorodeoxyglucose PET-CT in every volunteer, whereas ephedrine failed to stimulate BAT. Thus, at doses leading to broad activation of the sympathetic nervous system, ephedrine does not stimulate BAT in humans. In contrast, mild cold exposure stimulates BAT energy expenditure with fewer other systemic effects, suggesting that cold activates specific sympathetic pathways. Agents that mimic cold activation of BAT could provide a promising approach to treating obesity while minimizing systemic effects.